The impact of individual variations in taste sensitivity on coffee perceptions and preferences - Masi, Camilla; Dinnella, Caterina; Monteleone, Erminio; Prescott, John (Physiology & behavior, 2015)
Despite a few relationships between fungiform papillae (FP) density and 6-n-propylthiouracil (PROP) taster status have been reported for sensory qualities within foods, the impact on preferences remains relatively unclear. The present study investigated responses of FP number and PROP taster groups to different bitter compounds and how these affect coffee perception, consumption and liking. Subjects (Ss) with higher FP numbers (HFP) gave higher liking ratings to coffee samples than those with lower FP numbers (LFP), but only for sweetened coffee. Moreover, HFP Ss added more sugar to the samples than LFP Ss. Significant differences between FP groups were also found for the sourness of the coffee samples, but not for bitterness and astringency. However, HFP Ss rated bitter taste stimuli as stronger than did LFP Ss. While coffee liking was unrelated to PROP status, PROP non-tasters (NTs) added more sugar to the coffee samples than did super-tasters (STs). In addition, STs rated sourness, bitterness and astringency as stronger than NTs, both in coffee and standard solutions. These results confirm that FP density and PROP status play a significant role in taste sensitivity for bitter compounds in general and also demonstrate that sugar use is partly a function of fundamental individual differences in physiology. •Physiological measures underlying taste perception were investigated•The impact of physiological indices on coffee lixking and consumption was studied•Fungiform papillae density affects both taste perception and coffee preference•PROP taste status affects taste perception both in coffee and in standard solutions•Sugar use depends both on fungiform papillae density and PROP taste status